Microwave sensor response in relation to durian maturity - Suttapa, S.; Varith, J.; Krairiksh, M.; Noochuay, C.; Phimpimol, J. (My University, 2009)
This research studied the microwave response in relation to maturity development of durian fruit (Durio zibethinus Murry cv. Monthong) using a microwave sensor at frequency of 2.45 GHz. The microwave sensor applied two patch antennas to couple the microwave signal from durian. The experiment was conducted on 30 intact durian fruits at 91-123 days after full-bloom. One intact fruit on the tree was attached with the microwave sensor onto durian peel. The microwave sensor response was recorded everyday. Meanwhile, three durian fruits with the same size and age were picked from the tree for every third day to determine their maturity indices e.g., reducing sugar, starch, moisture content, dry matter and dielectric properties of durian pulp. Result showed that the microwave sensor response linearly decreased during the first period day 91-103, then linearly increased during day 104-118. As the wave from microwave sensor penetrated through the peel, it may interact to one of the maturity indices in the pulp, possibly moisture content during maturity of 50- 70% maturity and starch content during maturity of 70-90%. Dielectric constant of durian pulp at 2.45 GHz was found as a confound factor affecting microwave sensor response relating to durian maturity. The transition of microwave response was approximately at day 103, implying that durian maturity was about 70%, corresponding to an onset of reducing sugar. The microwave responses may be beneficial for durian farmers to predict the suitable harvesting period because of its nondestructive characteristic for durian maturity prediction.
Keywords: Dielectric properties; Durian; Maturity; Microwave sensor; Non-destructive